Scientific Visualization: The Visual Extraction of Knowledge from Data - Bonneau, Georges-Pierre; Ertl, Thomas; Nielson, Gregory M. (Mathematics and Visualization,, 2006)
How to master, organize and extract useful knowledge from the overwhelming flow of information made available by today's data acquisition systems and computing resources has become one of the greatest scientific challenges of the 21st century. Visualization is the premium means of taking up this challenge. This book is based on selected lectures given by leading experts in scientific visualization during a workshop held at Schloss Dagstuhl, Germany. Topics include user issues in visualization, large data visualization, unstructured mesh processing for visualization, volumetric visualization, flow visualization, medical visualization and visualization systems. The book contains more than 350 color illustrations.